1999
DOI: 10.1038/sj.sc.3100859
|View full text |Cite
|
Sign up to set email alerts
|

Successful intrathecal ethanol block for intractable spasticity of AIDS-related progressive multifocal leukoencephalopathy

Abstract: Objective: To study the e cacy of intrathecal ethanol block to relieve intractable spasticity in AIDS-related progressive multifocal leukoencephalopathy (PML) when long-term intrathecal baclofen infusion cannot be used. Methods: A 33-year-old man with AIDS-related PML developed very severe spastic paraparesis (Ashworth rigidity score, 4) and painful muscle spasms. The patient was unable to sit in his wheelchair and remained bed bound. Combined oral baclofen and tizanidine at therapeutical doses were used witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…11,12 Early publications reported that the injection of 45% alcohol into the muscle either at the motor points or by large quantities nonspecifically into the muscle resulted in decreased spasticity without the loss of voluntary movement or loss of sensation. The intrathecal injections have been used as a final step in the care of severely spastic individuals.…”
Section: Indicationsmentioning
confidence: 99%
“…11,12 Early publications reported that the injection of 45% alcohol into the muscle either at the motor points or by large quantities nonspecifically into the muscle resulted in decreased spasticity without the loss of voluntary movement or loss of sensation. The intrathecal injections have been used as a final step in the care of severely spastic individuals.…”
Section: Indicationsmentioning
confidence: 99%